Glycine and glycine receptor signalling in non-neuronal cells - Van Den Eynden, Jimmy; SahebAli, Sheen; Horwood, Nikki; Carmans, Sofie; Brône, Bert; Hellings, Niels; Steels, Paul; Harvey, Robert J.; Rigo, Jean-Michel (Frontiers in Molecular Neuroscience, 2009)
Glycine is an inhibitory neurotransmitter acting mainly in the caudal part of the central nervous system. Besides this neurotransmitter function, glycine has cytoprotective and modulatory effects in different non-neuronal cell types. Modulatory effects were mainly described in immune cells, endothelial cells and macroglial cells, where glycine modulates proliferation, differentiation, migration and cytokine production. Activation of glycine receptors (GlyRs) causes membrane potential changes that in turn modulate calcium flux and downstream effects in these cells. Cytoprotective effects were mainly described in renal cells, hepatocytes and endothelial cells, where glycine protects cells from ischaemic cell death. In these cell types, glycine has been suggested to stabilize porous defects that develop in the plasma membranes of ischaemic cells, leading to leakage of macromolecules and subsequent cell death. Although there is some evidence linking these effects to the activation of GlyRs, they seem to operate in an entirely different mode from classical neuronal subtypes.